Papal justice: subjects and courts in the Papal State, 1500 - 1750 - Fosi, Irene (Catholic Univ. of America Press, 2011)
A complex geography -- Roman tribunals in the early modern period -- The "new" inquisition and the pope's city -- The theater of justice -- Restless nobles -- Collaboration and conflicts : governors, bishops, inquisitors -- Sins and crimes -- Inside the family -- Disciplining the clergy -- Buon governo : between Utopia and reality -- Little fatherlands : local identity and central power -- Rivers of ink : petitions, memorials, letters -- Justice represented, justice recounted